9.2: A Novel Lamination Process for Flexible AMOLED Encapsulation. Issue 1 (June 2015) - Wang, Tao; Zhang, Song; Sun, Tao; Du, Xiao‐bo; Gao, Jing; Zhou, Wei‐Feng; Wang, Da‐Wei
Abstract : In order to decrease the bending radius of flexible OLED, an ultra‐thin barrier film (UTBF) was developed and applied on the 4.8 inch flexible AMOLED display for reduce the total thickness of the panel. Furthermore, a novel transfer lamination process assisted with a thermal release adhesive was applied into the encapsulation process with a high‐precision alignment system. The cathode‐peeling risk during display lift‐off process and bending process declined remarkably. The storage lifetime of the AMOLED is more than 240 hours at 60 °C and 90% RH and the bending times reached to 10, 000 times at a 4mmφ radius.